Aging aggravated liver ischemia and reperfusion injury by promoting STING‐mediated NLRP3 activation in macrophages. Issue 8 (14th July 2020) - Zhong, Weizhe; Rao, Zhuqing; Rao, Jianhua; Han, Guoyong; Wang, Ping; Jiang, Tao; Pan, Xiongxiong; Zhou, Shun; Zhou, Haoming; Wang, Xuehao
Abstract: Although aggravated liver injury has been reported in aged livers post‐ischemia and reperfusion (IR), the underlying mechanism of innate immune activation of aged macrophages is not well understood. Here, we investigated whether and how Stimulator of interferon genes (STING) signaling regulated macrophage proinflammatory activation and liver IR injury. Mice were subjected to hepatic IR in vivo. Macrophages isolated from IR‐stressed livers and bone marrow‐derived macrophages (BMDMs) from young and aged mice were used for in vitro studies. Enhanced nucleotide‐binding domain and leucine‐rich repeat containing protein 3 (NLRP3) activation was found in both livers and macrophages of aged mice post‐IR. NLRP3 knockdown in macrophages inhibited intrahepatic inflammation and liver injury in both young and aged mice. Interestingly, enhanced activation of the STING/ TANK‐binding kinase 1 (TBK1) signaling pathway was observed in aged macrophages post‐IR and mitochondria DNA (mtDNA) stimulation. STING suppression blocked over‐activation of NLRP3 signaling and excessive secretion of proinflammatory cytokines/chemokines in the mtDNA‐stimulated BMDMs from aged mice. More importantly, STING knockdown in macrophages abrogated the detrimental role of aging in aggravating liver IR injury and intrahepatic inflammation. Finally, peripheral blood from the recipients undergoing liver transplantation was collected and analyzed. The results showed that the elderly recipients had much higher levels of TNF‐α, IL‐6, IL‐1β, and IL‐18 post‐transplantation, indicating increased NLRP3 activation in lR‐stressed livers of elderly recipients. In summary, our study demonstrated that the STING‐NLRP3 axis was critical for the proinflammatory response of aged macrophages and would be a novel therapeutic target to reduce IR injury in elderly patients. Abstract : Liver IR triggered mtDNA release from stressed hepatocytes. Aging promoted STING over‐activation, leading to enhanced NLRP3 inflammasome activation and increased proinflammatory cytokines/chemokines production of macrophages, which ultimately aggravated IR injury.